2018
DOI: 10.1016/j.cmi.2018.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Aetiology of lower respiratory tract infection in adults in primary care: a prospective study in 11 European countries

Abstract: A bacterial pathogen is identified in approximately one in five adult patients with LRTI in primary care, and a viral pathogen in just under half, with mixed infections in one in ten. Penicillin-resistant pneumococci and β-lactamase-producing H. influenzae are uncommon. These new findings support a restrictive approach to antibiotic prescribing for LRTI and the use of first-line, narrow-spectrum agents in primary care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
125
7
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(140 citation statements)
references
References 29 publications
(28 reference statements)
3
125
7
5
Order By: Relevance
“…The majority of acute respiratory infections is caused by viruses, such as rhinovirus (RV), influenza (INF) A and B viruses, metapneumovirus (MPV), and respiratory syncytial virus (RSV) [4]. However, in 20-62% of the patients, no pathogen is detected [46]. This might be the result of diagnostic failures or even infection by unknown pathogens, such as the Middle East respiratory syndrome coronavirus (MERS-CoV), that was first recognized in 2012 [7].…”
Section: Introductionmentioning
confidence: 99%
“…The majority of acute respiratory infections is caused by viruses, such as rhinovirus (RV), influenza (INF) A and B viruses, metapneumovirus (MPV), and respiratory syncytial virus (RSV) [4]. However, in 20-62% of the patients, no pathogen is detected [46]. This might be the result of diagnostic failures or even infection by unknown pathogens, such as the Middle East respiratory syndrome coronavirus (MERS-CoV), that was first recognized in 2012 [7].…”
Section: Introductionmentioning
confidence: 99%
“…A first phylogenetic analysis, including 147 genomes from various streptococci of the mitis group (SMG) species, was performed to classify 24 isolates collected from lower-respiratory tract infections (LRTI) within the EU project GRACE (22) which we suspected to be S. pseudopneumoniae (n=16) or S. mitis (n=3), or for which no definitive classification was possible to obtain using traditional typing methods and MLSA (n=5) (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…While SPPN_RS06420 had a G+C content challenging for the design of PCR primers (average of 27.1%) further analysis of SPPN_RS10375 and its surrounding intergenic regions in the 44 genomes indicated that this 627-bp locus could be a good candidate for a molecular marker. 8 clinical isolates, not subjected to whole-genome sequencing, and collected during the same LRTI study (22), that were either impossible to identify (n=4) or suspected to be S. pseudopneumoniae (n=4), were found to be positive by PCR for SPPN_RS10375, indicating they are all S. pseudopneumoniae . These strains were also positive for the recently published S. pseudopneumoniae marker SPS0002 (12) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations